Masker Gratis dan Informasi Social Distancing Bagi Masyarakat Dusun Motong Are Tengah - ., Indrawati; Risfianty, Dwi Kartika; Fitriah, Leny (INTAN CENDEKIA (Jurnal Pengabdian Masyarakat), 2020)
Covid-19 is a type of virus that can easily spread through aerosols and airbones. The rapid spread of covid-19 since March 2020 in Indonesia caused the government and the people of Indonesia to experience panic. A number of people experienced panic buying in buying masks so that many of the people were unable to use masks due to the scarcity of masks on the market. In addition to the use of masks, the government also applies rules that require people to do social distancing. However, the government's policy to use masks and social distancing as an effort to break the spread of the Covid-19 chain is still largely ignored by the public. This service aims to provide free masks to the community and provide information about social distancing. The method for carrying out this Community Service activity is by directing the chairman and all members of Community Service from house to house.